Protecting Victims Privacy in Cinematographic Works: A Juridical Analysis of Freedom of Expression in the Film ‘Vina Sebelum 7 Hari’: Perlindungan Hak Privasi Korban dalam Karya Sinematografi: Analisis Yuridis terhadap Kebebasan Berekspresi dalam Film ‘Vina Sebelum 7 Hari’ - Sunan Autad Sarjana; Atifah Rohmah Fani; Hifdhotul Munawaroh; Iman Nur Hidayat; Rashda Diana (Journal of Indonesian Comparative of Syari'ah Law, 2026)
Films serve as educational media and convey moral messages, but they differ when they portray the true story of a victim of sexual violence by exposing their true identity without protection. The film "Vina Sebelum 7 Hari" depicts the real-life case of sexual violence experienced by Vina, with explicit scenes that depict the victim's traumatic experience and reveal her identity to the public. This potentially violates legal norms regarding the protection of the victim's identity, as stipulated in Article 69 (d) of Law No. 12 of 2022 concerning Criminal Acts of Sexual Violence, the Pornography Law, the Broadcasting Law and the Protective data Personal law. The exposure of the victim's identity causes secondary psychological impacts, social stigma, and psychological distress for the victim and her family. Although the film is intended to have educational value and moral awareness, its presentation without adequate protection actually brings harm to the victim and society such as Article 69 letter (d) of Law No. 12 of 2022 concerning on the Crime of Sexual Violence, Article 10 of Law No. 44 of 2008 concerning on Pornography, Article 48 Paragraph 4 of Law No. 32 of 2002 concerning on Broadcasting and Law No. 27 of 2022 concerning on Personal Data Protection. This study uses a normative-juridical method and use analysis qualitative to discuss the legal protection of the identity of victims of sexual violence in the context of film screenings, examining aspects of TPKS, Pornography laws, Broadcasting law. Using secondary data source with primary, secondary and tertiary legal materials and using qualitative data analysis methods in order to produce more accurate reaserch.